DEGRADATION KINETICS OF ANTHOCYANINS IN ACIDIC AQUEOUS EXTRACTS OF BERRIES - L. M. Soldatkina; V. O. Novotna; I. Salamon (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2017)
The effect of pH, light and temperature on degradation of anthocyanins in acidic aqueous extracts of chokeberries, elderberries and blackberries was studied. The degradation of anthocyanins in berry extracts under influence of pH, light and temperature followed the first-order reaction kinetics. Anthocyanins of chokeberry extracts had the highest values of rate constants of degradation. Anthocyanins of blackberry extracts had the highest values of half-life time. The temperature dependences of the rate of anthocyanin degradation were described by the Arrhenius equation. Activation energies of anthocyanin degradation were 5.7, 10.1 and 15.0 kJ/mol at pH=2, respectively, for chokeberry, elderberry, and blackberry аnthocyanins.